Modelling the thickness of landfast sea ice in Prydz Bay, East Antarctica. Issue 1 (15th October 2015) - Yang, Yu; Zhijun, Li; Leppäranta, Matti; Cheng, Bin; Shi, Liqiong; Lei, Ruibo
Abstract: Landfast sea ice forms and remains fixed along the coast for most of its life time. In Prydz Bay, landfast ice is seasonal due to melting, mechanical breakage and drift of ice in summer. Its annual cycle of thickness and temperature was examined using a one-dimensional thermodynamic model. Model calibration was made for March 2006 to March 2007 with forcing based on the Chinese National Antarctic Research Expedition data, which consisted of in situ ice and snow observations and meteorological records at the Zhongshan Station. The observed maximum annual ice thickness was 1.74 m. The ice broke and drifted out in summer when its thickness was 0.5–1.0 m. Oceanic heat flux was estimated by tuning the model with observed ice thickness. In the growth season, it decreased from 25 W m -2 to 5 W m -2, and in summer it recovered back to 25 W m -2 . Albedo was important in summer; by model tuning the estimated value was 0.6, consistent with the ice surface being bare all summer. Snow cover was thin, having a minor role. The results can be used to further our understanding of the importance of landfast ice in Antarctica for climate research and high-resolution ice–ocean modelling.